PENGARUH KEGIATAN LABORATORIUM BERBASIS MODEL 5E TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI ASAM BASA - Firza Luthfia Adlina; Tritiyatma H; Irma Ratna Kartika (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This research aims to determine the effect of laboratory activities based on 5E model against student’s concept understanding on acid-base material. This research was conducted in senior high school of 76 Jakarta in the even semester. The method of this research was experiment research. The sample of this research taken by purposive sampling technique, so that got two classes that were XI MIA 3 as experiment class and XI MIA 1 as control class. Experimental class was given treatment in the form of laboratory activity based on model 5E (engagement, exploration, explanation, elaboration, and evaluation), while for control class using laboratory activity without based on 5E model. The instrument used in the research was a post-test question in the form of student's concept comprehension test, consisting of 20 multiple choices question and 3 essays questions. The average of experimental class test result was 65.01 while the average of control class test result was 51.28. Data obtained was analyzed using non-parametric statistics Mann-Whitney test, showed the result that value of Zcount = 1.51 smaller than Ztable/α = 1.64 or Zcount<Ztable. That is, implementation of 5E model based laboratory activity has a positive effect against student’s concept understanding on acid-base material. Keywords: Acid-Base Solution, Laboratory Activities, Learning Cycle 5E (Model 5E)